Konsep Kesatuan Usaha : Pendekatan Socioemotional Wealth dan Family Embeddedness - Kristianti, Ika; Charita, Nindya Permata; Prastyo, Bagus Dwi (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2020)
The purpose of this study is to analyze and make conclusions about the concept of business unity that will be associated with socioemotional wealth and family embeddedness. This study will portray SMEs from the concept of business entity. This study uses Social-Emotional Wealth (SEW) and Family Embeddedness (FE). There are five dimensions in SEW and three dimensions in FE. This research uses qualitative research with the object of research of several food and beverage and batik UKM in Salatiga and Surakarta. The selection of research objects is based on the length of the business and the family's business management. The technique used in this study was an interview with six people as key informants. The results showed that the majority of SMEs in this study had applied the concept of a business entity. The social-emotional wealth approach has a bigger role than the kinship family approach because external factors trigger the development of SMEs in maintaining their business continuity more and internal factors of family members actually reduce company performance because they are prone to conflict and thus costs. that happened was bigger.